Transparent fluoride glass-ceramics with phase-selective crystallization for middle IR photonics. Issue 36 (12th September 2022) - Zhang, Longfei; Sun, Yang; Jiang, Yiguang; Da, Bo; Du, Juan; Wang, Shuaipeng; Qi, Sisheng; Yang, Zhiyong; Zhang, Long; He, Jin
Abstract : We fabricate transparent fluoroindate glass-ceramics with phase-selective crystallization (SrF2, CaF2 and MgF2 ) using a general one-step strategy. The ab initio molecular dynamics provide fundamental insights into phase-separation at the atomic scale. Abstract : Crystallization in glass is a fundamental topic in materials science, yielding the beauty and richness of crystals in glass for broad applications. However, controlling the crystallization in fluoride glasses remains a challenge owing to their low glass-forming ability. We fabricate transparent fluoroindate glass-ceramics (FGCs) with phase-selective crystallization (SrF2, CaF2 and MgF2 ) by a general one-step strategy. The alkaline-earth cations with high field strength are utilized to engineer the phase separation which induce subsequent phase-selective crystallization. The ab initio molecular dynamics revealed the heterogeneous distribution of Sr/Y–F regions and diverse diffusion rates of different elements in fluoride glass melt, providing fundamental insights into phase-separation at the atomic scale. Rapid quenching is employed to regulate the crystal growth in spontaneous crystallization during the cooling stage. The crystal morphology, element distribution, lattice parameters and simulated atomic structure in FGCs further elucidate the phase-separation mechanism, thermodynamics and kinetics in rapid quenching. The new FGCs manifest enhanced mechanical and chemical stability and do not sacrifice the excellent optical performance compared to the parent fluoroindate glass. Numerous optical applications with superior properties in MIR photonics have been demonstrated. This sets the stage for phase-separation chemistry to yield a diverse selection of desired crystals precipitated from fluoride glass.